2014
DOI: 10.2134/jeq2013.11.0469
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Cadmium Phytoavailability and Human Bioaccessibility for Vegetables Exposed to Soil or Atmospheric Pollution by Process Ultrafine Particles

Abstract: When plants are exposed to airborne particles, they can accumulate metals in their edible portions through root or foliar transfer. There is a lack of knowledge on the influence of plant exposure conditions on human bioaccessibility of metals, which is of particular concern with the increase in urban gardening activities. Lettuce, radish, and parsley were exposed to metal-rich ultrafine particles from a recycling factory via field atmospheric fallouts or polluted soil. Total lead (Pb) and cadmium (Cd) concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(40 citation statements)
references
References 71 publications
2
35
1
2
Order By: Relevance
“…However, recent studies have also reported metal uptake by plants via foliar transfer (Uzu et al 2010;Schreck et al 2012a, b). According to Xiong et al (2014a), foliar uptake of Cd and Pb due to particulate matter deposition is of particular importance near recycling factories.…”
Section: Bioavailability Of CD In Soilmentioning
confidence: 99%
“…However, recent studies have also reported metal uptake by plants via foliar transfer (Uzu et al 2010;Schreck et al 2012a, b). According to Xiong et al (2014a), foliar uptake of Cd and Pb due to particulate matter deposition is of particular importance near recycling factories.…”
Section: Bioavailability Of CD In Soilmentioning
confidence: 99%
“…These concentrations cannot only be credited to soil-to-plant transfer. Aerial deposition onto leaves and fruits could explain such results [21,22]. Moreover, with the increasing quantities of ultrafine atmospheric particles in urban and peri-urban areas, foliar plant exposure could sometimes be the main route of plant pollution in aerial organs [23,120].…”
Section: Lack Of Data About Sb Localization In Plant Organsmentioning
confidence: 99%
“…The human bioaccessible fraction of a metal(loid) is defined as the fraction extracted by the entire digestive system when it is ingested with polluted soil [158], or polluted vegetables [20,21]. A standardized bioaccessibility test has been developed by the BioAccessibility Research Group of Europe (BARGE): the Unified BARGE Method (UBM) [159].…”
Section: Human Bioaccessibility Of Sbmentioning
confidence: 99%
See 1 more Smart Citation
“…Lead does not play any known necessary function in living 1 The article is published in the original. metabolism, and is reported to cause a number of toxic effects to metabolic reactions in living organisms [7,8].…”
Section: Introductionmentioning
confidence: 99%